(untitled) (Global Journal of Management and Business Research, 2013)
Purpose: The paper aims at finding out the movement of certain macro-economic variables in India. The variables are FDI inflow, GDP, Market rate and CPI Inflation rate. Design/Methodology: To study the linear relationship, the paper uses simple correlation coefficient and coefficient of determination. Along with it, for further prediction regression analysis is used. For an overview, measures of central tendency, standard deviation and graphical representations are used. Significance level between the variables is tested using t-test. Findings: The variables are linearly related to one another. In other words, the variables are highly correlated and there is significant correlation coefficient among them. Practical Implication: The findings may be used as an input for Economic and Budgetary decision making. Research Limitation: Limited variables are used for the study. External noise may present because of exclusion of other variables.